PENGARUH BEAUTY VLOGGER LIPPIELUST TERHADAP BRAND AWARENESS PRODUK SECONDATE - Rachma Ayu Nadia; Rah Utami Nugrahani (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
The number of social media users and beauty enthusiasts in Indonesia can be used by makeup companies to promote their products by advertising on social media using a beauty vlogger. The presence of social media makes it easier for beauty vloggers to provide information about the world of beauty, especially makeup. Lippielust is one of the beauty vloggers in Indonesia who often discusses about lip products or is known as a professional lip swatcher. The products discussed are local brands which run out within 7 minutes after launching, namely Secondate. The purpose of this study was to determine how much the impact of Lippielust as beauty vlogger towards Secondate’s brand awareness. Data analysis technique used is descriptive analysis, simple linear regression analysis, and hypothesis test. According to the results of hypothesis testing, beauty vlogger Lippielust has a significant impact towards audience response, as shown by tcount > ttable (12,609 > 1,6599). Based on coefficient determination, beauty vlogger lippielust has 60,9% impact towards audience response, while 39,1% influenced by other factors not examined in this study